2016
DOI: 10.1242/dev.129254
|View full text |Cite
|
Sign up to set email alerts
|

The late and dual origin of cerebrospinal fluid-contacting neurons in the mouse spinal cord

Abstract: Considerable progress has been made in understanding the mechanisms that control the production of specialized neuronal types. However, how the timing of differentiation contributes to neuronal diversity in the developing spinal cord is still a pending question. In this study, we show that cerebrospinal fluid-contacting neurons (CSF-cNs), an anatomically discrete cell type of the ependymal area, originate from surprisingly late neurogenic events in the ventral spinal cord. CSF-cNs are identified by the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
118
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(146 citation statements)
references
References 104 publications
16
118
1
Order By: Relevance
“…Adult ependymal cells are originated from the Nkx6.1+/Gata2+/Gata3+ ventral spinal progenitors and maintain Nkx6.1 expression4041. In consistent with these studies, we observed that CR2-GFP+ ependymal cells of adult spinal cord were positive for Nkx6.1 and Notch1 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Adult ependymal cells are originated from the Nkx6.1+/Gata2+/Gata3+ ventral spinal progenitors and maintain Nkx6.1 expression4041. In consistent with these studies, we observed that CR2-GFP+ ependymal cells of adult spinal cord were positive for Nkx6.1 and Notch1 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…A small number of ELCs within the regenerating spinal cord also express TUJ1. Of note, these TUJ1+ cells demonstrate a staining pattern similar to that observed in the developing mouse spinal cord (Petracca et al, ) and suggest that some ELCs of the regenerate tail demonstrate neuronal‐like properties. Taken together, our SOX9 and TUJ1 data strongly support the idea that regenerate spinal cord ELCs are a heterogeneous population.…”
Section: Discussionsupporting
confidence: 69%
“…To confirm the absence of neurons in regenerated tails, we immunostained with the neuronal markers NeuN and HuC/D (Figure ). Whereas NeuN is considered to be a marker of mature neurons within the spinal cord, HuC/D is expressed by mature and immature neurons, as well as some neuronal‐like cell types (e.g., cerebrospinal fluid contacting (CSF‐c) cells; (Marichal, García, Radmilovich, Trujillo‐Cenóz, & Russo, ; Petracca et al, ). As expected, NeuN immunopositive (+) cells were present throughout the grey matter of the original spinal cord (Figure a, b), but entirely absent from the fully regenerated spinal cord (Figure c, d).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because phenotypic similarities-and thus, similarities in gene expression-can also arise by convergent or concerted evolution (2), validation of the proposed homologies will require more extensive molecular characterization, including the functional validation of transcription factor involvement in cell-type specification and, ideally, single-cell transcriptomics for an unbiased account of all cellular modules used by each type (35). The proposed ancient nature of a neuron-type clade specified by a Gata1/2/3-Tal CoRC finds support by recent studies showing that the same transcription factors are also expressed in Kolmer-Agduhr neurons in fish (23) and in the corresponding central spinal fluid-expressing neurons in mouse (36). KolmerAgduhr neurons are hair cell-like sensory neurons that contact the central canal and send out ipsilateral ascending axons (37).…”
Section: Discussion Cellular-resolution Expression Atlases For Complementioning
confidence: 92%